Pertanggungjawaban Pidana terhadap Mucikari dan Perlindungan Hukum Anak Korban Pekerja Seksual (Studi Putusan Nomor 327/Pid.Sus/Pn.Bgl) - Saptia Novandie; Ridwan Ridwan; Aliyth Prakarsa (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Cases of exploitation of children have continued to increase in the last few years. The world of children should be colored by playing activities, learning and developing their interests and talents for the future, not to be exploited both exonomically and sexually. In the Bengkulu District Court decision Number Number 327/Pid.Sus/2020/Pn.Bgl Defendant Heny Susanti Binti Hermansyah has sexually and economically exploited children who are 16 years old by employing them as sex workers in the defendant’s massage parlor. The judge sentenced him to sexual exploitation, but the defendant’s actions were not only sexual exploitation but also economic exploitation. This has prompted researchers to examine how criminal accountability is for pimps who exploit children as sexual workers ( Study Putusan : 327/Pid.Susu/2020/Pn.Bgl) and how is the legal protection for child victims of sexual workers. This study uses the theory of criminal responsibility and legal protection theory end normative juridical research methods with qualitative reasearch te results of this study are that the defendat named Heny Susanti Binti Hermansyah should not only be punished for economic exploitation, but the defendant should be punished for economic exploitation of children as well as providing compenstation against victims who have been harmed by the defendant. Prosecutors should include elements releted to criminal acts of economic exploitation, not only sexual exploitation, in accordance with Law No. 35 of 2014 concerning Child Protection Article 76I. And in the Article 98 of the Criminal Prosedure Code stipulates that if an act that forms the basis of an indictment in an examination of a criminal case by a District Court causes harm to another person, then the presiding judge of the session at the request of that person may decide to combine the claim for compenstation to the cases the crime. So that the victim gets legal protection in the form of compenstation in the form of Remuneration, Restitution, Rehabilitation, Treatment of the actions that have been carried out by the defendant as the owner of a massage parlor who has exploited children as sex workers